TRANSFORMING TRADITIONAL TEACHING METHODS THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Neykova, Melina; Ivanova, Adelina (Innovation in Woodworking Industry and Engineering design, 2025)
Today’s educational institutions are facing constant challenges related to the avalanche of developments in the process of integrating digitalization technologies and forming "smart" e-learning environments, including those based on artificial intelligence (AI). The advent of AI technologies has had a profound impact on educational processes, precipitating a paradigm shift in conventional teaching methodologies. In this context, AI can be regarded as a valuable instrument capable of executing a multitude of operations intrinsic to university activities. Unfortunately, the dynamism of this process is very high, and the speed at which AI platforms have been generated has been increasing rapidly in recent years, while educational institutions still lack the practices, skills and readiness to operate and implement the various AI tools successfully. In this regard, the presented study provides an overview and comparative analysis of various specialized online AI-platforms that are available online and can be used both by teachers in their professional and pedagogical activities and by students, supporting the process of choosing and integrating AI-based technologies in teaching and educational activities.